"What Is Right for Me, Is Not Necessarily Right for You": The Endogenous Factors Influencing Nonparticipation in Medical Assistance in Dying. (August 2021) - Brown, Janine; Goodridge, Donna; Thorpe, Lilian; Crizzle, Alexander
Access to medical assistance in dying (MAID) is influenced by legislation, health care providers (HCPs), the number of patient requests, and the patients' locations. This research explored the factors that influenced HCPs' nonparticipation in formal MAID processes and their needs to support this emerging practice area. Using an interpretive description methodology, we interviewed 17 physicians and 18 nurse practitioners who identified as non-participators in formal MAID processes. Nonparticipation was influenced by their (a) previous personal and professional experiences, (b) comfort with death, (c) conceptualization of duty, (d) preferred end-of-life care approaches, (e) faith or spirituality beliefs, (f) self-accountability, (g) consideration of emotional labor, and (h) future emotional impact. They identified a need for clear care pathways and safe passage. Two separate yet overlapping concepts were identified, conscientious objection to and nonparticipation in MAID, and we discussed options to support the social contract of care between HCPs and patients.